Depth-correlated backscattered electron signal intensity for 3D-profile measurement of high aspect ratio holes. (6th August 2019) - Sun, Wei; Ohta, Hiroya; Ninomiya, Taku; Goto, Yasunori; Sohta, Yasunari
Abstract: In-line metrology for measuring 3D features of the high aspect ratio (HAR) holes is becoming more challenging due to the progressing semiconductor technology, particularly in memory devices. Measurements of the bottom critical dimension (CD), taper angles and 3D profiles of the HAR holes require new imaging capabilities. In this work, we explored the characteristics of high-energy backscattered electron (BSE) signals and demonstrated their promising application to 3D metrology. From Monte Carlo simulation results, it is worth noting that BSE signal intensity emitted from an irradiated location in the depth of the hole decreases exponentially with the increase of the depth from the top surface (perpendicular depth) of the hole. Furthermore, the influences of various factors including the electron energy, the depth and the sidewall angle (SWA) of the hole on the attenuation of the BSE signal intensity were investigated. The simulation results show that the attenuation of the BSE signal intensity depends on the electron energy, the depth and the density of the hole but is independent of the SWA and the incident angle of the primary electron beam. Based on the characteristics of the BSE signal intensity, an algorithm was proposed for the 3D metrology of the HAR holes. Finally, the differences in CDs between the measured value and the target value of HAR holes with various geometries were examined. A maximum measurement bias within ±2.0 nm for various holes with different depths, densities and SWA values shows great potential of depth-correlated BSE signals in 3D metrology.